Infection Strategies of Bacterial and Viral Pathogens through Pathogen–Human Protein–Protein Interactions - Durmus Tekir, Saliha; Cakir, Tunahan; Ulgen, Kutlu (Frontiers in Microbiology, 2012)
Since ancient times, even in today's modern world, infectious diseases cause lots of people to die. Infectious organisms, pathogens, cause diseases by physical interactions with human proteins. A thorough analysis of these interspecies interactions is required to provide insights about infection strategies of pathogens. Here we analyzed the most comprehensive available pathogen-human protein interaction data including 23,435 interactions, targeting 5,210 human proteins. The data were obtained from the newly developed pathogen-host interaction database, PHISTO. This is the first comprehensive attempt to get a comparison between bacterial and viral infections since the bacterial data have been scarce until the last few years. We investigated human proteins that are targeted by bacteria and viruses to provide an overview of common and special infection strategies used by these different pathogen types. We observed that in the human PPI network the proteins targeted by pathogens have higher connectivity and betweenness centrality values than proteins not interacting with pathogens. The preference of interacting hub and bottleneck proteins is found to be a common infection strategy of all types of pathogens to manipulate human essential mechanisms. Specifically viruses tend to interact with human proteins of much higher connectivity and centrality values in the human protein network than bacteria. Gene Ontology enrichment analysis of the human proteins targeted by pathogens indicates crucial clues about the infection mechanisms of bacteria and viruses. Bacteria interact with human proteins that are enriched in immune response to disrupt human defense mechanisms whereas viruses manipulate human cellular processes in order to use that transcriptional machinery for their own genetic material transcription. As a novel observation about pathogen-human systems, the human proteins targeted by both pathogens are shown to be enriched in the regulation of metabolic processes.